A new combination and a new species of Andean Mutisieae (Asteraceae) - Sancho, Gisela (2005)
Gochnatia lanceolata was described on the basis of two collections: the type (Carolina 01) from Peru and a paratype (Torrico & Peca 336) from Bolivia. The morphological characters analyzed here (e.g. style branches, apical anther appendages, phyllaries, pollen, and leaf anatomy) show that these specimens belong to different taxa. A new combination in Chucoa (Chucoa lanceolata) is proposed for the type collection from Peru. A new species, Gochnatia angustifolia, is described on the basis of the paratype from Bolivia.